PERAN SPORT MASSAGE DALAM PENCEGAHAN DAN PENANGANAN CEDERA PADA ATLET - Lolina Endah Prastiwi; Lolita Endah Prasiwi; Regita Dwi Cahyani; Sofia Rahmawati; ZIhan Novita Sari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2026)
Sports injuries remain a major barrier to sustained athletic performance because they disrupt training continuity, delay return-to-play, and increase the risk of recurrent injury. Objective: This systematic literature review examined the role of sport massage in preventing and managing sports injuries among athletes. Methods: Literature published between 2020 and 2025 was searched using Google Scholar, Crossref, PubMed, ScienceDirect, and DOAJ/SINTA with combinations of the terms “sport massage”, “massage therapy”, “sports injury”, “injury prevention”, “recovery”, “delayed-onset muscle soreness”, and “range of motion”. Article selection followed the PRISMA stages of identification, screening, eligibility, and inclusion. Results: Ten studies met the inclusion criteria and were synthesized thematically. The evidence indicates that sport massage contributes to muscle recovery, pain reduction, improved blood circulation, increased flexibility and range of motion, psychological relaxation, and reduced risk of recurrent injury. However, the strongest evidence is still concentrated on minor injuries, delayed-onset muscle soreness, and short-term recovery, while evidence for chronic injuries and long-term performance remains limited. Conclusion: Sport massage can be positioned as a complementary preventive and rehabilitative strategy in athlete development programs, provided that its application is integrated with exercise therapy, load management, and professional supervision. Key words: Sport Massage, Sports Injury, Prevention, and Management. Cedera olahraga merupakan salah satu faktor penghambat utama dalam pencapaian dan keberlanjutan performa atlet karena dapat mengganggu kontinuitas latihan, memperlambat proses kembali bertanding, serta meningkatkan risiko cedera berulang. Tujuan kajian ini adalah menganalisis peran sport massage dalam pencegahan dan penanganan cedera pada atlet melalui pendekatan systematic literature review. Literatur yang diterbitkan pada rentang 2020-2025 ditelusuri melalui Google Scholar, Crossref, PubMed, ScienceDirect, dan DOAJ/SINTA dengan kombinasi kata kunci “sport massage”, “massage therapy”, “sports injury”, “injury prevention”, “recovery”, “delayed-onset muscle soreness”, dan “range of motion”. Seleksi artikel mengikuti tahapan PRISMA, yaitu identification, screening, eligibility, dan included. Sebanyak 10 artikel memenuhi kriteria inklusi dan dianalisis melalui sintesis tematik. Hasil kajian menunjukkan bahwa sport massage berkontribusi terhadap pemulihan otot, penurunan nyeri, peningkatan sirkulasi darah, fleksibilitas, range of motion, relaksasi psikologis, serta penurunan risiko cedera berulang. Namun, bukti terkuat masih berada pada konteks cedera ringan, delayed-onset muscle soreness, dan pemulihan jangka pendek, sedangkan bukti pada cedera kronis dan keberlanjutan performa jangka panjang masih terbatas. Dengan demikian, sport massage layak ditempatkan sebagai strategi komplementer dalam program pencegahan dan rehabilitasi cedera atlet, terutama jika dikombinasikan dengan terapi latihan, manajemen beban latihan, dan supervisi profesional Kata kunci: Sport Massage, Cedera Olahraga, Pencegahan, dan Penanganan.